2016
DOI: 10.2527/jas.2015-9592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding diets containing distillers' dried grains with solubles and wheat middlings with equal predicted dietary net energy on growth performance and carcass composition of growing–finishing pigs1

Abstract: This experiment evaluated the effects of feeding distillers' dried grains with solubles (DDGS) and wheat middlings (WM) in diets with similar estimated NE content on growth performance and carcass characteristics of growing-finishing pigs. Pigs ( = 384; 29.1 ± 3.6 kg initial BW) were blocked by initial BW, and within blocks, pens were randomly allotted to 1 of 4 dietary treatments (8 pigs/pen and 12 replicates/treatment) in a 4-phase feeding program (29 to 50, 50 to 75, 75 to 100, and 100 to 120 kg BW). Dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
5
9
1
Order By: Relevance
“…The ADG in the present study was 773 g/d at the 100% feeding level, whereas ADG in previous studies ranged from 560 to 900 g/d [2931]. The ADG improved as the feeding level increased.…”
Section: Discussioncontrasting
confidence: 68%
“…The ADG in the present study was 773 g/d at the 100% feeding level, whereas ADG in previous studies ranged from 560 to 900 g/d [2931]. The ADG improved as the feeding level increased.…”
Section: Discussioncontrasting
confidence: 68%
“…The observation that wheat DDGS did not affect dressing percentage is in contrast with Thacker (2006) who reported that 25% wheat DDGS reduced dressing percentage. The lack of an impact of wheat DDGS subcutaneous fat depth is in agreement with observations from studies with corn DDGS ( Whitney et al, 2006 ; Wu et al, 2016 ). Rate of glycolysis postmortem is linked to incidence of PSE meat with an increased risk associated with a rapid pH decline postmortem.…”
Section: Discussionsupporting
confidence: 89%
“…These values are within the acceptable analytical limits according to the Association of American Feed Control Officials (AAFCO, 2014), given 17 mg/kg of Cu was provided by the trace mineral premix and the Cu provided by other ingredients used in formulation. For diet characteristics, the by-product diet decreased bulk density of the diet by an average of 7.4% compared to the corn-soy diet, which is similar to others whom fed diets containing 30% or more of by-product ingredients (Wang et al, 2007, Asmus et al, 2014Wu et al, 2016).…”
Section: Chemical Analysissupporting
confidence: 77%
“…Added Cu did not increase HCW or HCW ADG, which is not consistent with previous research completed by Coble et al (2017). However, the reduction in HCW and carcass yield for pigs fed the by-product diet compared to those fed the cornsoy diet is consistent with most published literature (Asmus et al, 2014;Graham et al, 2014b;Wu et al, 2016). By-product ingredients generally contain high amounts of dietary fiber and have a low bulk density, which increases gut fill and weight in the large intestine (Turlington, 1984;Asmus et al, 2014).…”
Section: Carcass Characteristicssupporting
confidence: 45%